(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
English is an important language used for worldwide communication and academic performances. However, proficiency levels in English vary significantly due to a range of socioeconomic factors. This study explores how socioeconomic background influences the proficiency of English language between students in 10th and 12th grade schools in Kerala. The study involves a sample of 384 respondents from 8 different schools in Kerala, including 225 students, 100 parents and 59 teachers. Employing a mixed method approach, the study investigates how family location, economic status, siblings’ and parents’ educational backgrounds and language of communication within the family affect students’ English language proficiency. Yamane’s formula is used to calculate the sample size. Data is collected through interviews and organized questionnaires. The data collected is examined utilizing qualitative methods, including descriptive statistics, regression analysis and inferential statistics. The study finds a strong positive correlation between English language proficiency and family background factors. Specifically, the parents educational background significantly enhances students’ English language proficiency with a beta coefficient of 0.970. Students from urban areas exhibit higher proficiency indicated by a beta coefficient of 0.985. Economic status reflects that higher income levels facilitate better educational support with a beta coefficient of 0.981. The language of communication within families also significantly impacts English language proficiency with a beta coefficient of 0.984. These findings demonstrate that socioeconomic factors substantially improve the English language proficiency.